The Concept of Qalb Al-Dayn (Debt Restructuring) and its Contemporary Issues in Islamic Banking Practices - Hasan, Aznan; Haron, Muhamad Nasir; Mohamed, Mohd Faysal; Mana, Budeeman (2016)
Nowadays, debt restructuring are among the important aspects in financial system including Islamic financial institutions. The purpose of these exercises are varied, among other are to stabilise certain situation of financial distress of customers and to allow customers to take advantages of or benefit from certain market movement. There are a number of debt restructuring methods used. Among others is qalb al-dayn where it refers to the practice of restructuring the existing debt with new debt where the proceeds from this new debt will be used to settle the existing debt facility. This exercise may raise several Sharī‘ah concerns. Thus, this paper aims at investigating the permissibility of qalb al-dayn from Shariah perspective. The paper begins with a brief overview of the debt restructuring, its rationale and current practice in Islamic banking and finance. The paper also discusses the qalb al-dayn from Sharī‘ah point of view. This paper adopts the legal research methodology where the data used were largely library-based (documentary). In this vein, opinions of jurists, classical and contemporary will be analysed in discussing this practice of qalb al-dayn in Islamic financing facilities. Several resolution of various Islamic financial institutions, will also be analysed in this study. Based on the analysis conducted on this method, this study revealed that the jurists, classical and contemporary are unanimously agreed that there shall be no qalb al-dayn for those insolvent debtors (Mu’sir). Nonetheless, the jurists have different opinions with regards to practice of qalb al-dayn for solvent debtors (Musir), where some allows it subject to fulfilment of conditions and some even allows it without any restrictions. Finally, the paper concludes that in some cases of Islamic banking cases the category of defaulters do not necessary fall under both solvent and insolvent debtor thus need to further research to be accomplished to justify it from Shariah perspective.